Patients with haemolytic uraemic syndrome caused by Escherichia coli O157: absence of antibodies to Vero cytotoxin 1 (VT1) or VT2. Issue 11 (November 1993) - Chart, H; Law, D; Rowe, B; Acheson, D W
Abstract : Serum samples from 30 patients with haemolytic uraemic syndrome (HUS), caused by Escherichia coli O157, and 30 apparently healthy volunteers, were used to examine the immune response of patients to Vero cytotoxins (VT) 1 and VT2. Patients' sera could not be differentiated from control sera using ELISA; and using immunoblotting, none of the sera had antibodies reactive with either the A or B subunits of VT1 or VT2. Examination of sera for antibodies to VT1 and VT2 seems to be of little value in the serodiagnosis of HUS caused by Vero cytotoxin-producing E coli O157.